Beetween Notifications and Social Interaction: Mindfulness, Self Control, and Phubbing in Teenagers - Puspitasari, Ivana; Huwae, Arthur (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Adolescents in Indonesia’s digital era face new psychological challenges due to intensive smartphone use, one of which is phubbing behavior, defined as ignoring face-to-face interactions in favor of focusing on a smartphone. This study aims to investigate the roles of mindfulness and self-control in influencing the level of phubbing behavior among adolescents. The research employed a quantitative approach using multiple regression analysis. The sample consisted of 410 adolescent active smartphone users with daily usage exceeding four hours, selected through purposive sampling. Research instruments included the Five Facet Mindfulness Questionnaire (FFMQ) (α = 0.660–0.861), the Brief Self-Control Scale (BSCS) (α = 0.81), and the Generic Scale of Phubbing (GSP) (α = 0.76). The results indicated that mindfulness and self-control jointly have a significant eflect on phubbing behavior. These findings highlight the importance of strengthening self-control as an eflort to reduce phubbing behavior among adolescents in the digital era and provide a foundation for the development of psychology-based intervention programs aimed at improving the quality of social interactions.Remaja era digital di Indonesia menghadapi tantangan psikologis baru akibat penggunaan smartphone yang intensif, salah satunya berupa perilaku phubbing yaitu mengabaikan interaksi tatap muka karena lebih fokus pada smartphone. Penelitian ini bertujuan untuk menyelidiki peran mindfulness dan kontrol diri dalam mempengaruhi tingkat perilaku phubbing pada remaja. Metode penelitian menggunakan pendekatan kuantitatif dengan analisis regresi berganda. Sampel penelitian berjumlah 410 remaja pengguna aktif smartphone dengan durasi penggunaan lebih dari 4 jam per hari, diperoleh melalui teknik purposive sampling. Instrumen penelitian meliputi Five Facet Mindfulness Questionnaire (FFMQ) (a = 0,660–0,861), Brief Self-Control Scale (BSCS) (a = 0,81), dan Generic Scale of Phubbing (GSP) (a = 0,76). Hasil penelitian menunjukkan bahwa mindfulness dan kontrol diri secara bersama-sama berpengaruh signifikan terhadap perilaku phubbing. Temuan ini mengimplikasikan pentingnya penguatan kontrol diri dalam upaya mengurangi perilaku phubbing pada remaja era digital, serta memberikan landasan bagi pengembangan program intervensi berbasis psikologi untuk meningkatkan kualitas interaksi sosial.